A SURVEY ON PERFORMANCE OF FREE SPACE OPTICAL COMMUNICATION LINK - Thakur, Er. Sushila; Thakur, Er. Rajeev (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The modern era of communication needs a system with high bandwidth and high speed datarates.To fulfill rapid demands in today’s technology era, Free space optical (FSO) communication system has become very attractive technology, because they provides high bandwidth, license free spectrum using infrared beam, and are a reliable means of communications. The first part of the paper introduces the FSO system its block diagram and also the reason behind its usage. The second part informs about the factors which impairs the performance of the system. The third part will define the factors which enhance the performance of FSO system. The fourth part here will discuss which type of frequency is better for FSO system. The last part will describe about the different modulation techniques and which modulation is good for FSO system.